PERBEDAAN PENGARUH BRAINGYM DAN LATIHAN KINESTETIK TERHADAP PROPIOCEPTIVE PADA ANAK USIA 4-6 TAHUN DI TPA AL MUSTAQIM - Fatmawati, Veni; Khotimah, Siti; Imania, Dika Rizki (Sport and Fitness Journal, 2015)
The age of 4-6 years are the time for children to play so the best stimulation should be implemented through games. They have not experienced the sensomotoric maturation which affects concentration, posture, balance and daily behavior. It is necessary to perform treatment as early as possible in the form of brain gym and kinesthetic exercises, which usually used both gross motoric skills and sensory. The study aims to determine the effect of brain gym and kinesthetic exercises for proprioceptive in 4-6 years old children. The number of respondents of this study were 48 children which were divided into 2 groups: group 1 with brain gym and group 2 with kinesthetic exercises. The treatment was routinely given 3 times a week for one month. The research method is a Quasi experimental research which was designed using pre and post-test group design. Paired T test was the statistical test used for brain gym, Willcoxon test was used for kinesthetic exercises and Mann Whitney test was used for different test influences. The results of the data analysis using paired T test shows that the p-value was 0.000 (p <0.05). This means that there is an influence of brain gym on proioseptive in 4-6 years old children at TPA Al Mustaqim. The data analysis test using sig Wilcoxon rank test shows p-value of 0.000 (p <0.05), which means that there is an influence of kinesthetic exercises of proioseptive in 4-6 years old children at TPA Al Mustaqim. The data analysis result using Mann Whitney Difference Test shows p value of 0.787 (p> 0.05) which means that the difference in the effect of brain gym and kinesthetic exercises on propioceptive in 4-6 years old children at TPA Al Mustaqim. It is suggested in 4-6 years old children are given braingym and kinesthetic exercises so that propioceptive is increased and thus, the concentration, posture and balance of the child is also improved.
Keywords: braingym, kinesthetic exercises, propioceptive.